2022
DOI: 10.2188/jea.je20200346
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Concentration and the Incidence of Stroke in the General Japanese Population: The Jichi Medical School Cohort Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Bhupesh et al found that women with lower preoperative plasma hemoglobin concentrations exhibited increased susceptibility to stroke [13]. Similarly, a Japanese trial revealed that low hemoglobin concentrations were linked to an increased risk of stroke in adults [14]. Moreover, a metaanalysis provided compelling evidence supporting the association between admission anemia and both ischemic and hemorrhagic stroke, as well as elevated mortality rates related to stroke [15].…”
Section: Discussionmentioning
confidence: 99%
“…Bhupesh et al found that women with lower preoperative plasma hemoglobin concentrations exhibited increased susceptibility to stroke [13]. Similarly, a Japanese trial revealed that low hemoglobin concentrations were linked to an increased risk of stroke in adults [14]. Moreover, a metaanalysis provided compelling evidence supporting the association between admission anemia and both ischemic and hemorrhagic stroke, as well as elevated mortality rates related to stroke [15].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, their study did not consider the impact of renal function, TG, UA, PLT, and HGB on the relationship between the non-HDL-c ratio and incident stroke when adjusting covariates, unlike our research. However, previous studies have identified these variables as stroke risk factors ( 18 22 ). Furthermore, it is imperative to recognize that the application of linear regression analysis may be susceptible to the impact of non-linear associations, resulting in discrepancies in the established linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that this study only adjusted for age, smoking, gender, hypertension, body mass index (BMI), drinking, diabetes, and high-sensitivity C-reactive protein (hs-CRP) when analyzing the relationship between the non-HDL-c/HDL-c ratio and stroke. Other significant factors known to influence stroke, such as renal function ( 18 ), triglyceride (TG) levels ( 19 ), uric acid (UA) levels ( 20 ), platelet count (PLT) ( 21 ), and hemoglobin concentration (HGB) ( 22 ), were not accounted for in the analysis. Furthermore, the nature of the relationship between the non-HDL-c/HDL-c ratio and stroke, whether it is linear or non-linear, requires further investigation.…”
Section: Introductionmentioning
confidence: 99%